Implementation of Total Quality Management (TQM) in Organizations and Business - Shabrina Ayu Hananta; Jeni Susyanti (International Journal of Economics and Management Research, 2024)
This research aims to identify and analyze the application of Total Quality Management (TQM) and its relationship with businesses and organizations that contribute to the development of an organization's Business Process Management (BPM). The method used is a literature review of 30 research articles that can be accessed openly on Google Scholar with national and international indexes within the last 5 years. The conclusion was that TQM had a major influence on organizational and business practices in hospitals, educational institutions and companies. And has a positive effect on the dimensions of work motivation, innovation, employee performance, reward systems, organizational performance and other dimensions.